Optimizing UHPECC properties using MAA-based particle packing techniques with SCMs - K., Priyanka; O. M., Suganya (Frontiers in Built Environment, 2025)
This paper presents the development of Ultra High Performance Engineered Cementitious Composites (UHPECC) through optimized Supplementary Cementitious Materials (SCMs) blends with cement and silica sand. Utilizing the Modified Andreasen and Andersen (MAA) model with Water Film Thickness (WFT) and Paste Film Thickness (PFT) analysis improves flowability and strength, reducing experimental trials. Experimental results showed that optimizing mix proportions using WFT and PFT evaluations increased packing density by up to 35.78% and reduced pore volume by 88.2% in the UHPECC matrix. CT scan analysis revealed a pore percentage of 7.5% and a compressive strength of 70 MPa in the conventional mix (X). However, incorporation of SCMs in composites significantly decreased pore percentage from 7.5% to 0.89% and achieved a compressive strength of 134.72 MPa. This study highlights the important role of SCMs selection and optimal quantity in enhancing properties of UHPECC, including packing density, mechanical performance, and porosity reduction.